ANALISIS MODAL KERJA DAN PROFITABILITAS PT. BERAU COAL ENERGY Tbk - -, Rachmaniah - (EKONOMIA, 2017)
The use of working capital should be managed as effectively as possible so that the profitability of the company can be improved. Working capital management in a company is considered successful when working capital according to established standards, so as not to cause advantages or disadvantages and can provide a satisfactory ratio. Ratio analysis of the company's working capital is necessary to know and interpolate the short-term financial position of the company and examine the efficiency and use of working capital in the company. The formulation of the problem in this research is whether the increase of working capital turnover, the increase of inventory turnover and the increase of cash turnover is followed by the increase of profitability (Return On Equity) of PT. Berau Coal Energy Tbk. This study aims to analyze the increase of working capital turnover, inventory turnover, cash turnover on corporate profitability of PT. Berau Coal Energy Tbk. The hypothesis in this research is the increase of working capital turnover, the increase of inventory turnover and the increase of cash turnover followed by profitability of PT. Berau Coal Energy Tbk.The data analysis used is comparative analysis. Analysis conducted in this study there are 4 stages of work-capital rotation analysis (Turnover Capital Turnover), inventory turnover (Inventory Turnover), cash turnover (Cash Turnover) and analysis tool to measure profitability of PT. Berau Coal Energy Tbk is Return on Equity (ROE).The results revealed that of the three calculated turnover analysis is the turnover of working capital, inventory turnover and cash turnover, only inventory turns are able to predict profitability (ROE). The increase in inventory turnover is followed by an increase in profitability (ROE), but the increase in working capital turnover and cash turnover is not followed by an increase in ROE.The ratio of working capital turnover, inventory turnover and cash turnover not simultaneously have an effect on profitability, then the company must know the other ratios that can affect profitability. For the next researcher is suggested to use other variable beside variable of cash turnover, inventory turnover and cash turnover as variable affecting profitability.